An Insight to Nanoliposomes as Smart Radiopharmaceutical Delivery Tools for Imaging Atherosclerotic Plaques: Positron Emission Tomography Applications - Reabetswe Sebatana; Kahwenga D. Kudzai; Allan Magura; Amanda Mdlophane; Jan Rijn Zeevaart; Mike Sathekge; Maryke Kahts; Sipho Mdanda; Bwalya Angel Witika (Pharmaceutics)
Atherosclerosis is a chronic progressive disease which is known to cause acute cardiovascular events as well as cerebrovascular events with high mortality. Unlike many other diseases, atherosclerosis is often diagnosed only after an acute or fatal event. At present, the clinical problems of atherosclerosis mainly involve the difficulty in confirming the plaques or identifying the stability of the plaques in the early phase. In recent years, the development of nanotechnology has come with various advantages including non-invasive imaging enhancement, which can be studied for the imaging of atherosclerosis. For targeted imaging and atherosclerosis treatment, nanoliposomes provide enhanced stability, drug administration, extended circulation, and less toxicity. This review discusses the current advances in the development of tailored liposomal nano-radiopharmaceutical-based techniques and their applications to atherosclerotic plaque diagnosis. This review further highlights liposomal nano-radiopharmaceutical localisation and biodistribution—key processes in the pathophysiology of atherosclerosis. Finally, this review discusses the direction and future of liposomal nano-radiopharmaceuticals as a potential clinical tool for the assessment and diagnosis of atherosclerotic plaque.